Analisis Semantik Leksikal Pada Penggunaan Kata-Kata Teknis Fisika - Tamara Elisabet Gultom; Alom Maria Sagala; Claudia Tedja; Valentina Maringga (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research aims to carry out semantic analysis of technical words in the field of physics. The method used in this research is descriptive qualitative. Data collection techniques include library methods and observation of technical physics words, and semantic analysis using the Big Indonesian Dictionary (KBBI) and physics textbooks.